Surgical Treatment of Unusual Anatomy of the Tricuspid Valve in Ebstein’s Anomaly - Hanna V. Maistriuk; Iaroslav P. Truba; Serhii M. Boyko; Ivan V. Dziuryi (Ukrainian Journal of Cardiovascular Surgery, 2024)
Ebstein’s anomaly is a congenital heart disease in which the septal and posterior leaflets of the tricuspid valve are displaced to the apex of the right ventricle, forming its atrialization. In contrast, the anatomical position of the anterior leaflet usually remains normal.The aim. To present and analyze a case of surgical treatment of Ebstein’s anomaly with a rare anatomy – isolated displacement of the anterior leaflet of the tricuspid valve.Case report. We present a rare clinical case of isolated displacement of the anterior leaflet of the tricuspid valve into the right ventricular cavity with the formation of a right atrial aneurysm. The diagnosis was made prenatally and confirmed after the birth of the child by echocardiography. Surgical intervention was postponed and successfully performed at the age of six years due to the progression of tricuspid insufficiency and increase in the right atrial aneurysm. We achieved a reduction in the size of the right atrium (diameter 31 mm, volume 25 ml and area 10 cm2) and minimized insufficiency at the tricuspid valve. The total duration of the surgical intervention was 270 minutes. The intra- and postoperative periods were uneventful. The duration of the patient’s stay in the intensive care unit was 4 days. We believe that this pathology of the anterior leaflet of the tricuspid valve should be interpreted as a variant of Ebstein’s anomaly.Conclusion. Isolated tricuspid valve anterior leaflet displacement with right atrial aneurysm is amenable to surgical correction with good immediate and long-term results.